2005
DOI: 10.5194/acp-5-1773-2005
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of sulphuric acid to atmospheric particle formation and growth: a comparison between boundary layers in Northern and Central Europe

Abstract: Abstract. Atmospheric gaseous sulphuric acid was measured and its influence on particle formation and growth was investigated building on aerosol data. The measurements were part of the EU-project QUEST and took place at two different measurement sites in Northern and Central Europe (Hyytiälä, Finland, March-April 2003 and Heidelberg, Germany, March-April 2004). From a comprehensive data set including sulphuric acid, particle number size distributions and meteorological data, particle growth rates, particle fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 30 publications
9
132
4
1
Order By: Relevance
“…Therefore, indirect methods have been employed to estimate J of 1 nm cluster (J 1 ) from apparent nucleation rates (for example, J 3 which is the nucleation rate derived from particle concentrations in the size range >3 nm). The most commonly used method is based on the time shift (or time delay, Dt) by using the measured aerosol size distribution and by taking into account self-coagulation of small particles and scavenging due to coagulation with large particles [Dal Maso et al, 2005;Fiedler et al, 2005;Kerminen and Wexler, 1996;Kuang et al, 2008;Kulmala et al, 2004;Paasonen et al, 2009;Riipinen et al, 2007;Sihto et al, 2006;Stolzenberg et al, 2005;Weber et al, 1996]. In practice, H 2 SO 4 is considered as the aerosol precursor for this kind of time shift calculations, so by default this method also assumes that H 2 SO 4 is the only condensable species for aerosol formation.…”
Section: Evaluation Of Gr Pargan and J Parganmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, indirect methods have been employed to estimate J of 1 nm cluster (J 1 ) from apparent nucleation rates (for example, J 3 which is the nucleation rate derived from particle concentrations in the size range >3 nm). The most commonly used method is based on the time shift (or time delay, Dt) by using the measured aerosol size distribution and by taking into account self-coagulation of small particles and scavenging due to coagulation with large particles [Dal Maso et al, 2005;Fiedler et al, 2005;Kerminen and Wexler, 1996;Kuang et al, 2008;Kulmala et al, 2004;Paasonen et al, 2009;Riipinen et al, 2007;Sihto et al, 2006;Stolzenberg et al, 2005;Weber et al, 1996]. In practice, H 2 SO 4 is considered as the aerosol precursor for this kind of time shift calculations, so by default this method also assumes that H 2 SO 4 is the only condensable species for aerosol formation.…”
Section: Evaluation Of Gr Pargan and J Parganmentioning
confidence: 99%
“…More recent work from the same group, in collaboration with other colleagues, made in Atlanta, GA, Boulder, CO, Tecamac, Mexico, and Macquarie Island, Australia, have focused on the numerical relationship of nucleation rates (J) and [H 2 SO 4 ] [Kuang et al, 2008;McMurry and Eisele, 2005;. Longterm measurements of H 2 SO 4 have been made also in Europe, including Hyytiälä [Dal Maso et al, 2005;Fiedler et al, 2005;Sihto et al, 2006], Heidelberg [Fiedler et al, 2005] and Hohenpeissenberg [Birmili et al, 2000[Birmili et al, , 2003Paasonen et al, 2009]. These observations also showed that [H 2 SO 4 ] values typically were at the 10 6 -10 7 cm −3 range at noon, depending on the season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the concentration of H 2 SO 4 has been consumed in quantity, the NPF events would be interrupted. However, if sufficient concentrations of H 2 SO 4 were present in the atmosphere, nucleation could occur even under relatively high concentrations of preexisting particles (Fiedler et al, 2005). The production and concentration of H 2 SO 4 depend on the concentration of its precursors, SO 2 and OH (Mikkonen et al, 2011), where the OH concentration is dependent on the photolysis rate of O 3 by solar radiation in the 280-320-nm UVB range.…”
Section: Npf Events Under Relatively High Number Concentration Of Prementioning
confidence: 99%
“…This process would be further enhanced with the increase of the concentration of preexisting particles; therefore, NPF would not occur in severely polluted environment. However if sufficient concentrations of precursors to begin NPF are present in the atmosphere, nucleation can occur even under relatively high background levels of pre-existing particles (Fiedler et al, 2005).…”
Section: Npf Events Under Relatively High Number Concentration Of Prementioning
confidence: 99%